Fate of the capping agent of biologically produced gold nanoparticles and adsorption of enzymes onto their surface - Parastoo Pourali; Volha Dzmitruk; Miroslav Pátek; Eva Neuhöferová; Milan Svoboda; Veronika Benson (Scientific Reports, 2023)
Abstract Enzymotherapy based on DNase I or RNase A has often been suggested as an optional strategy for cancer treatment. The efficacy of such procedures is limited e.g. by a short half-time of the enzymes or a low rate of their internalization. The use of nanoparticles, such as gold nanoparticles (AuNPs), helps to overcome these limits. Specifically, biologically produced AuNPs represent an interesting variant here due to naturally occurring capping agents (CA) on their surface. The composition of the CA depends on the producing microorganism. CAs are responsible for the stabilization of the nanoparticles, and promote the direct linking of targeting and therapeutic molecules. This study provided proof of enzyme adsorption onto gold nanoparticles and digestion efficacy of AuNPs-adsorbed enzymes. We employed Fusarium oxysporum extract to produce AuNPs. These nanoparticles were round or polygonal with a size of about 5 nm, negative surface charge of about − 33 mV, and maximum absorption peak at 530 nm. After the adsorption of DNAse I, RNase A, or Proteinase K onto the AuNPs surface, the nanoparticles exhibited shifts in surface charge (values between − 22 and − 13 mV) and maximum absorption peak (values between 513 and 534 nm). The ability of AuNP-enzyme complexes to digest different targets was compared to enzymes alone. We found a remarkable degradation of ssDNA, and dsDNA by AuNP-DNAse I, and a modest degradation of ssRNA by AuNP-RNase A. The presence of particular enzymes on the AuNP surface was proved by liquid chromatography–mass spectrometry (LC–MS). Using SDS-PAGE electrophoresis, we detected a remarkable digestion of collagen type I and fibrinogen by AuNP-proteinase K complexes. We concluded that the biologically produced AuNPs directly bound DNase I, RNase A, and proteinase K while preserving their ability to digest specific targets. Therefore, according to our results, AuNPs can be used as effective enzyme carriers and the AuNP-enzyme conjugates can be effective tools for enzymotherapy.